Numerical studies on the seismic response of support hanger for building pipelines - Min Huang; Jun He; Jun Liu; Junsheng Huang; Wenbin Pan; Hao Wang (PLoS ONE, 2025)
This study presents the development of numerical models that integrate wire, shell, solid, and connector elements to assess the mechanical performance of support hanger systems under both pushover and seismic loading conditions. Specifically, the models incorporate axial connectors with low compression stiffness and high-tension stiffness to simulate the tension-only behavior characteristic of tension bars. Additionally, the seismic analysis models account for the influence of pipes. Utilizing these models, parametric studies were conducted to investigate the impact of key parameters, including connector thickness, connector angle, brace angle, spacing of support hanger, earthquake waves, and the peak acceleration. The findings provide valuable insights for researchers and engineers in the field.